Selection conditions of unknown solution of Burnett equations - Skakauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. И. Скакаускас. Условия отбора искомого решения уравнений Барнета V. Skakauskas. Barneto lygčių ieškomo sprendinio atrankos sąlygos